Aβ pathology downregulates brain mGluR5 density in a mouse model of Alzheimer. (1st May 2018) - Lee, Minkyung; Lee, Hae-June; Park, In Suh; Park, Ji-Ae; Kwon, Yeon Ju; Ryu, Young Hoon; Kim, Chul Hoon; Kang, Joo Hyun; Hyun, In Young; Lee, Kyo Chul; Choi, Jae Yong
Abstract: The aim of the present study was to evaluate functional changes of mGluR5 expression in advanced Alzheimer's disease (AD) using positron emission tomography (PET) with an mGluR5 specific radiotracer ([ 18 F]FPEB) in 5xFAD AD model. Subsequently, in the same animal, mGluR5 expression was quantified by immunoassay techniques. The non-displaceable binding potential values for mGluR5 was estimated by the Logan's graphical analysis. Brain PET imaging revealed that radioactivities in the hippocampus and the striatum were significantly lower in 5xFAD mice compared to control animals. Binding values were also significantly lowered in 5xFAD mice. This decline was validated by immunoblotting of protein isolates from brain tissues, as the mean band density for 5xFAD mice had a lower mGluR5 intensity than for wild type mice. These results indicated that mGluR5 levels in 5xFAD mice were down regulated in the limbic system. Graphical abstract: Highlights: Compared with control group, radioactivities in the mGluR5 rich regions such as hippocampus and striatum showed lower uptakes in the 5xFAD group. Binding potential values for 5xFAD group also lower than those in the control group. These PET findings were validated by immunoblotting. Down-regulation of mGluR5 in the AD mice was successfully identified by [ 18 F]FPEB PET.